2012
DOI: 10.1182/blood-2011-05-357319
|View full text |Cite
|
Sign up to set email alerts
|

R-Ras is required for murine dendritic cell maturation and CD4+ T-cell priming

Abstract: R-Ras is a member of the RAS superfamily of small GTP-binding proteins. The physiologic function of R-Ras has not been fully elucidated. We found that RRas is expressed by lymphoid and nonlymphoid tissues and drastically upregulated when bone marrow progenitors are induced to differentiate into dendritic cells (DCs). To address the role of R-Ras in DC functions, we generated a R-Rasdeficient mouse strain. We found that tumors induced in Rras ؊/؊ mice formed with shorter latency and attained greater tumor volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 51 publications
(63 reference statements)
4
40
0
Order By: Relevance
“…In yet another study activated R-Ras activated p38 indirectly by promoting TGFb signaling (Erdogan et al, 2008). Finally, immune cells lacking R-Ras were shown to display decreased p38 activity (Singh et al, 2012). The mechanism underlying how R-Ras influences p38 in neurons is not known at present.…”
Section: Resultsmentioning
confidence: 99%
“…In yet another study activated R-Ras activated p38 indirectly by promoting TGFb signaling (Erdogan et al, 2008). Finally, immune cells lacking R-Ras were shown to display decreased p38 activity (Singh et al, 2012). The mechanism underlying how R-Ras influences p38 in neurons is not known at present.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Flt3 could be implicated in cell survival (Singh et al, 2012) and local Csf-2, which seems to exert antiapoptotic effects in nonlymphoid tissue (Greter, Helft, et al, 2012; Hirata, Egea, Dann, Eckmann, & Kagnoff, 2010). …”
Section: Origin and Regulation Of DC Differentiationmentioning
confidence: 99%
“…In vivo studies have revealed crucial roles of R-Ras in blood vessel homeostasis, vascular regeneration, angiogenesis [36,37], and immune regulation [38]. The activity of R-Ras is controlled by semaphorin-plexin signaling which has mainly been studied in the context of neuronal axon guidance [39,40].…”
Section: Introductionmentioning
confidence: 99%